PROBLEMATIZATION OF THE CONCEPT «REGION» IN CONTEMPORARY SCIENTIFIC RESEARCH - Golovneva, E.V. (Perm Federal Research Centre Journal, 2015)
This paper deals with problematization of the concept “region” in contemporary scientific research in relation to the appearance of the new methodological approaches to consideration of the spatial phenomenon as well as relativity of the regional factors. This paper views the region not only as a geographical space but primarily as a social and cultural phenomenon with its own set of relations and discourses.